Effects of extrusion cooking on the dietary fibre content and Water Solubility Index of wheat bran extrudates. (16th April 2015) - Rashid, Summer; Rakha, Allah; Anjum, Faqir M.; Ahmed, Waqas; Sohail, Muhammad
Summary Instant study was an attempt to elucidate the suitability of wheat bran for extrusion cooking and to check the effect of different extrusion parameters on the dietary fibre profile as well as on water solubility index. Response surface methodology was used to optimise the extrusion parameters. From results, it was concluded that extrusion cooking had a positive effect on total and soluble dietary fibre. Whilst the insoluble dietary fibre decreased appreciably with the varying processing parameters, the decrease in insoluble fibre and increase in soluble fibre were probably due to disruption of covalent and noncovalent bonds in the carbohydrate and protein moieties leading to smaller and more soluble molecular fragments. Additionally, water solubility index was greatly enhanced by varying extrusion temperature and screw speed. Conclusively, the findings suggest the usefulness of extrusion cooking to beneficially modify the wheat bran for value addition.